Mortality and Loss to Follow-Up Among HIV-Exposed Infants After Option B+ Guideline Implementation in Amhara Regional State Referral Hospitals, Ethiopia - Kassaw, Mesfin Wudu; Abebe, Ayele Mamo; Abate, Biruk Beletew; Getu, Mikiyas Amare; Kassie, Ayelign Mengesha (Frontiers in Pediatrics, 2021)
Abstract Background: Prevention of mother to child transmission of HIV program (PMTCT) is a comprehensive approach that aimed to the wellbeing of all HIV infected women, to prevent new HIV infection among infants born to HIV positive mothers, and providing management for HIV positive women and infants. Nevertheless, there was considerably high attrition within the prevention of mother to child transmission programs that was merely because of loss to follow up followed by mortality. In resource limited countries, one third of infected children die before one year, and more than half of them die before two years. The aim of this study was to assess the prevalence or incidence of mortality and loss to follow up among infants born from HIV positive mothers in the Amhara regional state referral hospitals, Ethiopia. Methods: This study was conducted in five Amhara regional state referral hospitals’ prevention of mother to child transmission departments. A simple random sampling technique with proportional allocation was used to assess the outcomes of 221 exposed infants. A retrospective cohort design was used in selecting the 221exposed infants’ document from the referral hospitals of the region, Amhara. The exposed infants’ profiles were documented between January 01/2014 and May 30/2017. Results: This study described attrition (death and loss-to-follow-up) of exposed babies in PMTCT departments of Amhara regional state referral hospitals in Ethiopia. In this study, low LTFU with zero death was reported. Residence, immunization status of babies, and place of delivery were independent factors of LTFU. Conclusions: The cumulative incidence of mortality in this study was zero. This assured that the recommend option is substantial for the elimination of HIV-caused death in 2030 as per WHO plan. However, the cumulative incidence of LTFU was not zero.